(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2013)
Due to criminalization of politics there has been a gradual erosion of democratic values of public life. The Election Commissioner G.V.G Krishnamurty has gone on record to mention that the case is threatening to degenerate into a government of the criminals, for the criminals and by the criminals. Political corruption, political murders, undercutting, leg pulling, by politicians has become the order of the day. This set of politicians in India within the robes of legislators have thoroughly polluted Indian politics and democracy by making it a business proposition. This reason, inter alia, the outer shell of the Indian democracy is undamaged but it appears to be moth-eaten from inside. The entry of criminals within the floor of parliament created disorder, pandemonium within the House by showing their muscle power rather than power of wit which they completely lack. The criminals terrorize and rule and created a situation even the skinny demarcation between the politicians and criminals has disappeared. This work intends to research the matter of criminalization of politics and its effect on the assorted issues and institutions referring to working of the government and socio-political lifetime of the country. Criminalization of politics could be a problem which has generated from within the governmental system and is slowly trying to paralyze every democratic institutions of this country. Criminalization of politics has creeped so deep into the system that principles and ideas like Rule of law, political accountability, free and fair elections, democracy, freedom of speech and expression have lost their credence. Only a few elaborative studies are done on the topic of criminalization of Indian politics. So, it might naturally be a vital work to investigate the concept and its effect on the socio political fabric of the country. Likewise, this research work has also discussed the subsequent aspects keeping in mind the matter of criminalisation of politics in India.